Surgical treatment of hand deformities in multiple enchondromatosis: a case report - (:unkn) unknown (My University, 2006)
Multiple enchondromatosis (Ollier's disease) is a rare disease characterized by widespread enchondromas. In general, the short tubular bones of the hand are involved, with progressive lesions resulting in cosmetic problems and functional deformities. Diaphysectomy and reconstruction with structural autografts or allografts are usually recommended in the treatment of extensive enchondromas involving the fingers. Curettage and grafting and ray amputation are other surgical procedures that can be applied depending on the severity of involvement. A 25-year-old woman with enchondromatosis presented with severe swelling and deformities on her fingers in both hands. The majority of the lesions were managed by diaphysectomy and reconstruction with structural grafts; ray amputation, curettage and grafting were performed for more severe lesions. During a long-term follow-up (left hand 6 years, right hand 5.5 years) cosmetic and functional results were acceptable.
Keywords: Adult; Female; Humans; Radiography; Abnormalities, Multiple; Diagnosis, Differential; Edema; Finger Joint; Enchondromatosis; Hand Deformities, Acquired